Avoiding health worker infection and containing the coronavirus disease 2019 pandemic: Perspectives from the frontline in Wuhan. (July 2020) - Tang, Ling-hua; Tang, Shan; Chen, Xiao-liang; Zhang, Shi; Xiong, Yong; Chen, Rong; Li, Wei; Liu, Hui-min; Xia, Zhong-yuan; Meng, Qing-tao
Abstract: Coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused great public concern worldwide due to its high rates of infectivity and pathogenicity. The Chinese government responded in a timely manner, alleviated the dilemma, achieved a huge victory and lockdown has now been lifted in Wuhan. However, the outbreak has occurred in more than 200 other countries. Globally, as of 9:56 am CEST on 19 May 2020, there have been 4, 696, 849 confirmed cases of COVID-19, including 315, 131 deaths, reported to Word Health Organization (WHO). The spread of COVID-19 overwhelmed the healthcare systems of many countries and even crashed the fragile healthcare systems of some. Although the situation in each country is different, health workers play a critical role in the fight against COVID-19. In this review, we highlight the status of health worker infections in China and other countries, especially the causes of infection in China and the standardised protocol to protect health workers from the perspective of an anaesthesiologist, in the hope of providing references to reduce medical infections and contain the COVID-19 epidemic. Highlights: To analyze the causes of Chinese health worker infections at 3 stages of the epidemic. It's pivotal to improve the ability to respond to public safety emergencies. It's crucial to judge the epidemic situation timely and correctly. It's imperative to minimise contact and apply artificial intelligence for medics. Adequate personal protection is essential to protect health workers.